The Multiple Violation of Maxim in Doctor Strange in The Multiverse Film - Muhammad Agung Nugroho; Zainal Ariffin (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
This study aims to describe the multiple violations of maxims based on the cooperative principle at the utterances in Doctor Strange in the Multiverse of Madness film and the intended meanings in it. This type of study is a qualitative descriptive research. The data consisted of twenty utterances in the film that reflected the violation of maxims based on the cooperative principle. Data collection was carried out by observation which consisted of several stages, namely identifying and marking the violation of maxims in the speech in the film, grouping each data based on the type of violation of the maxims, then coding the data. Data analysis was carried out by describing the context in each utterance and then analyzing it using Cutting's maxim violation theory. The result shows that the speakers violating four multiple maxims (quantity, quality, relation, and manner) totally 11 data or 55%, three maxims ((quantity, relation, manner), (quantity, quality, manner), (quantity, quality, relation)) totally 7 data or 35%, two maxims (quantity and quality) totally 1 data or 5 %, and one maxim (quality) totally 1 data or 5%. The meaning of violation by the speaker is intended to avoid the conflict, to intimidate someone, and to create a lie.